2018
DOI: 10.4335/10.4335/16.1.1-24(2018)
|View full text |Cite
|
Sign up to set email alerts
|

Birds of a Feather or by Note? Ideological Nationalization of Local Electoral Manifestos in Belgium

Abstract: Until now, scholars trying to unravel the phenomenon of nationalization have seldom considered the local policy layer or the ideological dimension as their main subject. This paper, however, studies the ideological nationalization of Flemish local party branches. It applies the method of content analysis of electoral manifestos to the local elections and examines the programmatic overlaps between the party headquarter and its local branches. An innovative nationalization measure is introduced and subsequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Prior research on local manifestos has shown that there is no or very low vertical party coordination of manifestos (see Gross and Jankowski 2020 ); this means that the Land parties do not set the manifestos for municipal parties, as is the case with framework manifestos in Belgium or Spain, respectively (see van de Voorde et al. 2018 ).…”
Section: Studying Voting Age Sixteen In Germanymentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research on local manifestos has shown that there is no or very low vertical party coordination of manifestos (see Gross and Jankowski 2020 ); this means that the Land parties do not set the manifestos for municipal parties, as is the case with framework manifestos in Belgium or Spain, respectively (see van de Voorde et al. 2018 ).…”
Section: Studying Voting Age Sixteen In Germanymentioning
confidence: 99%
“…In other words, the politicians that decided on the lowering of the voting age are not the same politicians that have to decide whether and how to react to the new voting age threshold in their local campaigns. Prior research on local manifestos has shown that there is no or very low vertical party coordination of manifestos (see Gross and Jankowski 2020); this means that the Land parties do not set the manifestos for municipal parties, as is the case with framework manifestos in Belgium or Spain, respectively (see van de Voorde et al 2018).…”
Section: K 3 Studying Voting Age Sixteen In Germanymentioning
confidence: 99%
“…These may be structured or even copied verbatim from some template or model program provided by the party's headquarters (see e.g. Van de Voorde et al, 2018). To assess this, the absolute difference between the word use in a manifesto of a given branch and the word use in the manifestos of all the other branches of that party is calculated.…”
Section: Measuring Three Dimensionsmentioning
confidence: 99%
“…Measuring localism. How to measure the degree of localist orientation in election manifestos is a challenge for political scientists (Gross and Jankowski, 2020;Van de Voorde et al, 2018). 4 This article examines the extent to which programs focus on specific local issues (such as specific locations in the municipalities).…”
Section: Measuring Three Dimensionsmentioning
confidence: 99%
“…Gross, Jankowski 2020) or to compare important cleavages on the regional level (Alonso, Goméz, Cabeza 2013). However, there are only a few studies that have focused on an analysis of issue saliency at a lower level of governance (Ashworth & Boyne, 2000;Libbrecht et al 2009;van De Voorde et al 2018). This is even more true for the topic of housing, which has received only marginal attention, as was observed in a qualitative study of regional-level election programs (Vašát & Čermák 2016).…”
Section: Literature Overviewmentioning
confidence: 99%